Real balance effects, timing and equilibrium determination - Christian Stoltenberg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper examines whether the existence and the timing of real balance effects contribute to the determination of the absolute price level, as suggested by Patinkin (1949,1965), and if they affect conditions for local equilibrium uniqueness and stability. I show that there exists a unique price level sequence that is consistent with an equilibrium under interest rate policy, only if beginning-of-period money yields transaction services. Predetermined real money balances can then serve as a state variable, implying that interest rate setting must be passive - a violation of the Taylor-principle - for unique, stable, and non-oscillatory equilibrium sequences. On the contrary, when the end-of-period money stock facilitates transactions, the equilibrium displays nominal indeterminancy and equilibrium uniqueness requires an interest rate setting consistent with the Taylor-principle.
Keywords: E32; E41; E52; 330; Real balance effects; predetermined money; price level determination; real determinacy; monetary policy rules; flexible prices